Aortic dissection induced by licorice tablets overdose: a Case Report - Luo, Xin; Wang, Yuhan; Liu, Bin; Zhang, Duyi; Chai, Yanfen; Wang, Lijun (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the pathogenesis of aortic dissection induced by licorice tablet poisoning.MethodsA case of aortic dissection caused by poisoning by overtaking licorice tablets was reported. The patient’s medical history, laboratory examination, imaging results, and treatment process were analyzed, and the relevant literature was reviewed.ResultsThis case suggests that licorice poisoning is a potential risk factor for aortic dissection, which needs to be paid attention to in clinical practice. In the face of acute poisoning, in addition to paying attention to the conventional treatment measures of acute poisoning, we should pay more attention to the pharmacological mechanism of drugs and their induced complications to avoid subjective judgment and reduce misdiagnosis and abuse.